2021
DOI: 10.1016/j.spinee.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Spring distraction system for dynamic growth guidance of early onset scoliosis: two-year prospective follow-up of 24 patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…This implant has important advantages, such as the potential to further reduce the curve after insertion and the fact that it does not have to be periodically lengthened. The design of the SDS and its preliminary and 2-year follow-up clinical performance have recently been reported [15,16]. However, its provisional design is not yet fully optimised, as the connectors are used off-label and do not prevent the release of metal debris.…”
Section: Introductionmentioning
confidence: 99%
“…This implant has important advantages, such as the potential to further reduce the curve after insertion and the fact that it does not have to be periodically lengthened. The design of the SDS and its preliminary and 2-year follow-up clinical performance have recently been reported [15,16]. However, its provisional design is not yet fully optimised, as the connectors are used off-label and do not prevent the release of metal debris.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report on 24 patients with EOS (5 idiopathic, 7 congenital, 3 syndromic, 9 neuromuscular) and 2-year postoperative follow-up indicated that the concept of spring distraction can be feasible as an alternative to present growing spine solutions without the need for repeat lengthening. 25,26 Scoliosis correction and growth was maintained at follow-up; however, the rate of reoperations was high (17 of 24 patients) which indicates that this technique requires further improvement. Further longer-term investigations into the effectiveness, risk of revision surgery and complications are expected.…”
Section: Distraction-based Methodsmentioning
confidence: 97%
“…In this way, the technique aims to control the apical segments by local derotation and fusion, while allowing for proximal and distal spinal growth. In 2013, McCarthy et al 25 showed that the Shilla technique required fewer reoperations (3 versus 7) but resulted in reduced spinal growth (0.7 cm/year) and lesser scoliosis correction with higher complication rates compared to growing rods. Therefore, its use has become limited to selective cases which need apical control.…”
Section: Distraction-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cervical guide has been applied in two cases of spinal distraction and one case of emergency treatment. In our center, we use spring distraction as a growth guidance technique for severe deformities that cannot be controlled with less invasive techniques such as braces or halo vests [ 27 ]. For cervicothoracic congenital deformities especially, the technique has shown the potential to not only control but even to reduce the deformity [ 28 ].…”
Section: Clinical Applicationmentioning
confidence: 99%